The Relationship between Cortisol and the Hippocampal Volume in Depressed Patients – A MRI Pilot Study. (2016) - Moica, Theodor; Gligor, Adrian; Moica, Sorina
Abstract: Stress is responsible for increased cortisol levels in depression, affecting different areas of the brain, especially the prefrontal cortex and the hippocampus. Our paper is analysing the interrelation between cortisol – as a marker of neuroendocrine response to stress and the hippocampal volume subfields – as markers of neurogenesis and neuroplasticity theory. The main goal of the research was focused to investigate and to prove the relation between the increased level of cortisol and the reduced volume of hippocampus in depression. We measured the morning serum cortisol level in a fasting state. For the volume of the hippocampus all patients underwent a MRI of the brain examination. The investigations have shown that both the right and the left hippocampal volumes are reduced in MDD patients. Higher levels of cortisol are associated with lower hippocampal subfield volumes, especially on the right.